KIAI PONDOK PESANTREN MAHASISWA - Prayoga, Ari; Mukarromah, Ima Siti (Perkumpulan Sarjana Manajemen Pendidikan Islam Indonesia, 2018)
The success of pondok pesantren depends on the expertise, depth of knowledge, authority, managerial, and skills of the kiai as a Central figure in pesantren. This study aims to reveal the role, function, and leadership characteristics of scholars in the Pondok Pesantren Universal Al-Islami Bandung (PPMU) or Ma'had Universal Al-Islamy. This study uses qualitative methods through a case study approach with single-case design. The results of the study show that (1) the leadership role of kiai as an architecture, educator, manager, administrator, entrepreneur, climator, Agent of Social Control and Relationship is implemented in the agenda and internal program of pesantren institutions; (2) the leadership function is carried out by internalizing the vision and mission of the institution, the team building of pesantren human resources, the decision making organization and external control conflict of the pesantren through activities with the civitas, the entire pesantren community and around; (3) leadership characteristics that arise according to the implementation of its function roles are religious charismatic, intellectual, trustworthy and social humanist.